Associations between Psychosocial and Physiological Factors and Diabetes Health Indicators in Asian and Pacific Islander Adults with Type 2 Diabetes - Dongmei Li; Jillian Inouye; Jim Davis; Richard F. Arakaki (Nursing Research and Practice)
The associations between psychosocial and physiological factors and diabetes’ health indicators have not been widely investigated among Asians and Pacific Islanders. We hypothesize that health behaviour and depression are directly or indirectly associated with diabetes’ health indicators such as BMI, glycemic control, general health, and diabetes quality of life. Our hypothesis was tested through a structural equation modelling (SEM) approach. Questionnaires that assessed health behaviour, depression, general health, diabetes quality of life, and haemoglobin A1c (HbA1c), along with patients’ demographic information, were obtained from 207 Asian and Pacific Islander adults with type 2 diabetes. IBM SPSS Amos 20 was used for the SEM analysis at 5% level of significance, and the goodness fit of the SEM model was also evaluated. The final SEM model showed that diet and exercise and foot care had positive associations, while depression had a negative association with diabetes’ health indicators. The results highlighted the importance of exercise and depression in diabetes patients’ BMI, glycemic control, general health, and quality of life, which provide evidence for the need to alleviate patients’ depression besides education and training in diet and exercise in future intervention studies among Asians and Pacific Islanders with type 2 diabetes.